2017
DOI: 10.1021/acsnano.6b06385
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Encapsulation ofSaccharomyces cerevisiaein Silicate Matrices Creates Distinct Metabolic States as Revealed by Gene Chip Analysis

Abstract: In order to design hybrid cellular/synthetic devices such as sensors and vaccines, it is important to understand how the metabolic state of living cells changes upon physical confinement within three-dimensional (3D) matrices. We analyze the gene expression patterns of stationary phase Saccharomyces cerevisiae (S. cerevisiae) cells encapsulated within three distinct nanostructured silica matrices and relate those patterns to known naturally occurring metabolic states. Silica encapsulation methods employed were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
(172 reference statements)
1
24
0
Order By: Relevance
“…Most of the genes involved in "ribosome" in the Z. rouxii response to 60% w/v sugar concentration were downregulated. This response seems to be consistent with other yeasts under different stresses, for example, Zygosaccharomyces parabilii under lactic acid stress (Ortizmerino et al, 2018), Pichia pastoris under methanol stress, and S. cerevisiae response to silicon encapsulation stress (Fazal et al, 2017). For example, ribosomal protein encoding genes, RPS13 and RPL4B, were downregulated after 4 h ( Table 2) of extreme high sugar stress in Z. rouxii.…”
Section: Ribosomesupporting
confidence: 84%
See 1 more Smart Citation
“…Most of the genes involved in "ribosome" in the Z. rouxii response to 60% w/v sugar concentration were downregulated. This response seems to be consistent with other yeasts under different stresses, for example, Zygosaccharomyces parabilii under lactic acid stress (Ortizmerino et al, 2018), Pichia pastoris under methanol stress, and S. cerevisiae response to silicon encapsulation stress (Fazal et al, 2017). For example, ribosomal protein encoding genes, RPS13 and RPL4B, were downregulated after 4 h ( Table 2) of extreme high sugar stress in Z. rouxii.…”
Section: Ribosomesupporting
confidence: 84%
“…It is reported that cell synthesis ribosome requires energy, reducing gene expression associated with ribosome biogenesis and minimizing energy consumption (Fazal et al, 2017). Decreasing "ribosome" seems to be a general stress response in yeast (Fazal et al, 2017).…”
Section: Ribosomementioning
confidence: 99%
“…Compared to imprinting into polymers where cross-linkers are needed (Schirhagl et al, 2010), the formation of thin imprinted organosilicate films with good diffusional penetration, important for sensing driven applications, is generally easier to achieve. Since the pioneering studies of Carturan et al (2004) who encapsulated S. cerevisiae yeast cells into silica gel films and studied its catalytic activity, imprinting of whole cells into inorganic sol-gel matrices rather than polymers (Haupt, 2003) has become a widely proposed approach (Avnir et al, 2005;Eleftheriou et al, 2013;Fazal et al, 2017). These matrices have gained more interest lately for the creation of sensing devices (Borovicka et al, 2013;Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of the growth in confined space—compared to traditional bacterial growth in liquid or soft‐agar media—cannot be fully exploited, for example, through the control of quorum sensing in confinement . Here, we use a sol–gel process to confine bacteria while maintaining viability, proliferation and metabolic activity . In contrast to a recently reported approach in which a single matrix was used to integrate cascades, we show a modular assembly concept associating beads functionalized with different types of bacteria working in synergy and thereby creating versatile user‐defined artificial microbial consortia .…”
mentioning
confidence: 99%